Pengaruh Cash Flow, Profitabilitas, dan Solvabilitas terhadap Kebijakan Dividen pada Perusahaan Farmasi yang Terdaftar di BEI Tahun 2020–2024 - Rahmayani, Aisyah; Istiono, Istiono (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of cash flow, profitability, and solvency on dividend policy in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The research population consists of 38 pharmaceutical companies, while the sample includes six companies selected using purposive sampling based on predetermined criteria. The data analyzed are secondary data obtained from companies’ financial statements and annual reports. Hypothesis testing was conducted using multiple linear regression analysis. The partial test results indicate that cash flow does not have a significant effect on dividend policy. Similar findings are observed for profitability, measured by Return on Assets (ROA), and solvency, proxied by the Debt to Equity Ratio (DER), both of which show a significant effect on dividend policy. Furthermore, the simultaneous test results demonstrate that the three independent variables collectively have a significant effect on dividend policy. The Adjusted R-squared value of 0.463 indicates that cash flow, profitability, and solvency explain 46.3% of the variation in dividend policy, while the remaining 53.7% is influenced by other factors outside the research model. These findings suggest that dividend policy decisions in pharmaceutical companies tend to be driven more by long-term strategic considerations than by short-term financial performance indicators.